El cálculo de la prima única de riesgo mediante la medida de riesgo transformada proporcional del tanto instantáneo - Montserrat Hernández-Solís; Cristina Lozano Colomer; José Luis Vilar Zanón (Atlantic Review of Economics, 2013)
– The goal of this research is to obtain a premium calculation principle, for the life business, based on a coherent risk measure, distorted probabilities with the Wang distortion function in the form of power, called 'Proportional Hazards (PH) Transforms'. It justifies the recommendation of Solvency II to increase or decrease, according to the type of insurance chosen, the mortality instantaneous rate and thus get an implicitly surcharged premium to deal deviations of actual claims regarding expected. Whole life insurance has been selected for this research, and the premium risk has been calculated for the four accepted laws of survival, such as the first and second Dormoy, Gomperzt law and Makeham law.
Keywords: M20; 330; Implicit surcharge; Distortion function; Hazards transform risk; Law of survival; Coherent risk measure; Whole life insurance